The Medical Librarian and Computer-Assisted Instruction - Smith, Linda C. (1974)
The requirements for a computer-assisted instruction (CAI) system in terms of hardware, communications, software, and personnel are discussed, and unique characteristics of CAI are reviewed. Current CAI applications in the medical field include programs in undergraduate medical and dental education, training of nurses and physical therapists, units for interns and residents, and continuing education for physicians. Certain problems exist in the current state of the art, however, including unsatisfactory aspects of each of the system components. The potential role of the medical librarian as a member of a CAI personnel team is explored, and contributions he can make in program development, monitoring, and evaluation are suggested. Medical librarians may themselves have opportunities in the future to use CAI to develop library skills and special subject knowledge. It is proposed that introduction of CAI may have the additional benefit of encouraging increased use of on-line bibliographic retrieval systems.